Pengendalian Stunting Melalui Edukasi Pengolahan Ragam Makanan Sehat dari Bahan Lokal dan Pendampingan Posyandu di Kelurahan Bongsari, Kota Semarang (Kolaborasi UNNES - PT Phapros, Tbk): Stunting Preventin through A Training on Processing a Variety of Healthy Foods from Local Ingredients and Assistance for Posyandu Cadres in Kelurahan Bongsari, Semarang City (Collaboration of UNNES and PT Phapros, Tbk) - Kusumaningtyas, Ratna Dewi; Lestari, Yanesti Nuravianda; Handayani, Prima Astuti; Laila, Rachma Akmila; Salsabila, Anida; Rahmah, Aisyah Khalimatur; Putri, Silvia Nouvelia; Rachmadi, Moch Faizal; Jannah, Reni Ainun; Imani, Nadya Alfa Cahaya; Barita, Asyera Dewi; Kun, Stefania Orance; Nindita, Ariana Eka (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Stunting is among the national priority issue in the National Medium Term Development Plan (RPJMN). At the global level, stunting is also a priority based on the Sustainable Development Goals (SDGs), especially related to the 3rd and 2nd SDGs, namely "good health and well-being" and "zero hunger". In this regard, the Semarang City Government has targeted that by 2024 the city will be free of stunting or zero stunting. On the other hand, the city of Semarang still records quite significant stunting data, namely 912 cases in 2024. To achieve the target of zero stunting, a synergy between the government, community, universities and industrial corporate social responsibility is necessary and can be implemented through community service and empowerment activity. Kecamatan Semarang Barat is among the area which record a quite high stunting rates in Semarang city, namely 84 cases in January 2024. To reduce the stunting rate in Kecamatan Semarang Barat, especially Kelurahan Bongsari, is a synergy between universities (UNNES), industry (pharmaceutical company PT Phapros Tbk), and local government is developed through a community service activities. Community service activities has been carried out in the form of education on stunting awareness, training on processing a variety of healthy foods from local ingredients and training to increase the capacity of posyandu cadres in Kelurahan Bongsari. UNNES and PT Phapros Tbk team also contribute in the form of recipe book, vitamins, and anthropometry equipment.